Relocating literature: rereading the waste land from a sri lankan post-war perspective - Sivapalan, C.C.A.; Canista arthie, D. (University of Jaffna, 2012)
T.S. Eliot’s The Waste Land is a poem that deals with the post war conditions of Europe after the First World War. Even though the poem does not overtly appeal to the First World War, and a very few references are made on the First World War (the pub scene), an underlying reading of the poem proves that The Waste Land does have the First World war in its background. What Eliot sees as the waste of modern civilization-spiritual dryness, fruitless sex, illicit sexual affairs, sexual laxity, hopelessness, and psychological and cultural deterioration cannot be restrained only to the westerners of the twentieth century. It has resonance with all the post-war communities and especially to Northern Sri Lankans who had experienced a ferocious war for three decades. What this paper proposes is to relocate The Waste Land in post-war Sri Lanka. In clear terms this paper perceives the post war conditions of Sri Lanka from Eliot’s point of view, according to his poem - The Waste Land. The comparative analysis of The Waste Land and the post-war conditions of Sri Lanka: adopting the qualitative / descriptive methodology, employed unstructured interviews with the counselors and clients, informal data collection such as; collecting news from some reputed news papers and gathering information from some informal discussions, proves that the psychological deterioration that comes along with the war remains irreparable in the war torn areas in Sri Lanka for a long time. Winston Churchill’s claim “injuries were wrought to the structure of human society which a century will not efface”, (Hughes, 1961, pp-39) also confirms this idea. Further this paper attempts to create awareness to all about our present plight–the spiritual cultural and psychological deterioration, in which we all are facing a moral threat as well.
Keywords: The Waste Land